Inguinal hernia in a Continuous Ambulatory Peritoneal Dialysis Patient Practising â€œKapal Bhatiâ€ therapy - Chaurasia, R K; Rauniyar, S K (Journal of Nepal Health Research Council, 2013)
A 72 years elderly man, diagnosed case of end stage renal disease with hypertension stage II and anemia of chronic disease on continuous ambulatory peritoneal dialysis along with the supportive medicines and yoga therapy mainly Kapal Bhati, presented with slowly increasing swelling in left inguinal region for two months which used to subside in supine position and bulge during coughing, later involved ipsilateral side of scrotum also. Then he was diagnosed having left side direct inguinal hernia. And then switched to hemodialysis followed by hernioplasty. CAPD was started again after two weeks. Though inguinal hernia is common in elderly male with predisposing factors but its development has not been reported in association with Kapal Bhati therapy which has become recently popular therapy for many diseases. Keywords: Continuous ambulatory peritoneal dialysis; inguinal hernia; Kapal Bhati.